A Review of Optical Nondestructive Visual and Near-Infrared Methods for Food Quality and Safety. (24th March 2013) - Alander, Jarmo T.; Bochko, Vladimir; Martinkauppi, Birgitta; Saranwong, Sirinnapa; Mantere, Timo
Abstract : This paper is a review of optical methods for online nondestructive food quality monitoring. The key spectral areas are the visual and near-infrared wavelengths. We have collected the information of over 260 papers published mainly during the last 20 years. Many of them use an analysis method called chemometrics which is shortly described in the paper. The main goal of this paper is to provide a general view of work done according to different FAO food classes. Hopefully using optical VIS/NIR spectroscopy gives an idea of how to better meet market and consumer needs for high-quality food stuff.